2015
DOI: 10.1039/c5ta00715a
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed boron subphthalocyanine derivatives as acceptors for organic bulk-heterojunction solar cells

Abstract: We present solution-processed organic solar cells based on subphthalocyanine acceptors with strong light harvesting in the visible region and an efficiency up to 3.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 39 publications
5
71
0
Order By: Relevance
“…Derivatization has also led to altering the HOMO and LUMO such that the BsubPc can act as an electron accepting material within OPVs. As a result, BsubPcs have been explored as a possible replacement for the more typical fullerene‐acceptor‐based devices . More recent studies have identified certain BsubPc derivatives that are soluble enough in organic solvents to be solution‐deposited into organic electronics allowing the device fabrication to be more scalable …”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…Derivatization has also led to altering the HOMO and LUMO such that the BsubPc can act as an electron accepting material within OPVs. As a result, BsubPcs have been explored as a possible replacement for the more typical fullerene‐acceptor‐based devices . More recent studies have identified certain BsubPc derivatives that are soluble enough in organic solvents to be solution‐deposited into organic electronics allowing the device fabrication to be more scalable …”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“… Structures of electron donors and acceptors in all BsubPc‐containing, solution‐deposited OPV devices in literature …”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…When blended with the donor A61, the A64 molecule exhibited a high PCE performance of about 4.0% . Very recently, Ebenhoch and co‐workers designed and synthesized a novel nonfullerene small molecule acceptor A65 which was used to assemble the solar cells with three different donors (MEH–PPV, P3HT, and PTB7) . The device performance indicated that when the PTB7 acted as the donor, a higher PCE value of about 3.51% was obtained compared to the low efficiency of the other two donors of MEH–PPV(0.40%) and P3HT(1.10%).…”
Section: Nonfullerene Small Molecule Acceptorsmentioning
confidence: 99%
“…Nevertheless, only very recently, SubPc molecules have been demonstrated as electron acceptors in solution-processed BHJ solar cells. [13] Herein, we report four hexachlorosubphthalocyanines (SubPcCl6-X) bearing different axial substituents, i.e. chlorine and differently substituted phenoxy groups, as electron acceptors in BHJ solar cells.…”
mentioning
confidence: 99%